Work climate from the perspective of nurses: qualitative research - Kosydar-Bochenek, Justyna; Krupa, Sabina; Semań, Tomasz; Mędrzycka-Dąbrowska, Wioletta (Frontiers in Medicine, 2023)
Introduction This study aims to determine the nurses’ view of the work climate. A positive work climate is one of the keys determining factors in improving nurse outcomes and affects patient satisfaction with care. Methods In this qualitative research, a semi-structured interview was used to understand nurses’ perceptions of their work environment. The participants’ responses were recorded and transcribed. Between November and December 2021, 22 nurses participated in the study. Purposive sampling was used to choose nurses for the research, and interviews were performed with these nurses utilizing a semi-structured interview form. The interviews were analyzed using a theme analysis. Results The themes identified in the data centered on four dominant elements that together shaped the prevailing work climate: participation in making decisions, companionship, job satisfaction, and changes they expect. Conclusion It is necessary to implement meetings at the level of departments and hospitals, where employees will receive support from the authorities and learn how they can improve the working climate. Implications for nursing management Research findings on the working climate can help hospital managers makers design interventions to create a good working environment for nurses.